Expeditious Extraction of Histones from Limited Cells or Tissue Samples and Quantitative Top‐Down Proteomic Analysis. Issue 2 (3rd February 2021) - Holt, Matthew V.; Wang, Tao; Young, Nicolas L.
Abstract: Histones are the primary protein component of chromatin and are involved in virtually all DNA‐templated processes. Histones are abundantly post‐translationally modified by a variety of chromatin‐modifying machinery. These post‐translational modifications (PTMs) are recognized by a range of "reader" proteins, which recruit additional proteins to specific locations on chromatin and impart precise and powerful effects on gene regulation. Each PTM typically exerts a positive or negative effect on transcription, and recent studies have shown that histone PTMs function in a combinatorial histone code: that is, histone PTMs function in combination to exert precise DNA‐templated regulation. Thus, there is a need to identify and understand proteoforms, or unambiguously defined single protein molecules with all combinations of modifications. Top‐down proteomics is currently the only viable approach for identifying and quantitating histone proteoforms, and mass spectrometry instruments have become sufficiently powerful to perform these quantitative analyses in a robust and high‐throughput fashion. These recent innovations have enabled new experimental directions in chromatin research but have also introduced temporal and other constraints. This has led us to develop the protocols described here, which increase throughput, reduce sample requirements, and maintain robust quantitation. Although originally designed for high‐throughput quantitative top‐down proteomics, the protocols described here are useful for a wide range of chromatin biology applications. Starting with small amounts of cells or tissue, we describe two basic protocols for exceptionally rapid and efficient nuclei isolation, acid extraction of histones, and high‐performance liquid chromatography fractionation of histones into histone families. We additionally describe the quantitative top‐down proteomic analysis of histone H4 proteoforms. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Nuclei isolation and acid extraction of histones from mammalian cells in culture/tissues Basic Protocol 2 : HPLC fractionation of histones and histone H4 HPLC‐MS/MS Support Protocol : Preparation of intact H3 histone tails by Glu‐C digestion